The Development of BOLU BAPER as Adiwiyata Based Teaching Aids for Chemistry Learning - Uswatun Khasanah (Chemistry Education Department, 2021)
This research aims to examine the development of BOLU BAPER (Boneka Molekul Berbahan Kain Perca) (patchwork molecule doll) as Adiwiyata-based teaching aids for learning chemistry, the reviewer assessment on BOLU BAPER as Adiwiyata-based teaching aids for learning chemistry and the product eligibility based on the reviewers and the students’ assessment toward BOLU BAPER as Adiwiyata-based teaching aids for learning chemistry in SMKN 2 Gedangsari. This research is a Research and Development (RD) with five steps; analysis, design, development, implementation, and evaluation. The subject of this research is 26 grade X students of the Automotive Class in SMKN 2 Gedangsari. The result shows that the process of developing a BOLU BAPER as teaching aids consists of several steps; the process of creating, the process of preparing the reviewing instrument, and the process of product testing for the reviewer. The reviewer’s assessment showed a good result with a slight revis. The detail of score from the material expert is 85%, the media expert is 96,25% and the students are 82,76%. The validity test proved that BOLU BAPER is valid to be used as teaching aids for chemistry learning.